The Involvement of Academic Teachers in Business Activity (Poznań University of Economics and Business Example) - Furmańczyk, Joanna; Kaźmierczyk, Jerzy (Studia Oeconomica Posnaniensia, 2017)
Cooperation of the academic world and the business one is not an easy thing and it faces many obstacles, mainly of an organisational and financial nature. The needs and aspirations of both sides seem to be completely different. During last 30 years, the Polish economy and Polish enterprises transformed qualitatively and quantitatively. Foreign capital, new technologies, methods of production, and knowhow have been just a few of many factors which have caused business development. The academic sector in Poland has also changed. That is why there is a significant need to provide a steady university - business relationship and interaction. Of course, it is still hard to find the answer for the question concerning both sides' advantages of that cooperation and its determinants. It is worth considering, who is interested in that kind of relationship. In the article, the authors focus on academic teachers' needs and expectations concerning cooperation with the business sector. They make an attempt at finding the determinants of involvement in undertaking business activities. The data obtained during the empirical research conducted among academic teachers of the Poznań University of Economics and Business are presented. They are also a basis for creating and indicating the "be-in-business-integrated-indicator" (Zintegrowany Wskaźnik Ubiznesowienia, ZWU), which would measure the level of business activities undertaken by academic teachers. Basing on research data and analysing the literature, many problems in the academic and business sectors were diagnosed. Therefore, in the last part of the article, advice and solutions which could strengthen the collaboration between academic and business sectors are presented.